HBV DNA integration and somatic mutations in HCC patients with HBV-HCV dual infection reveals profiles intermediate between HBV- and HCV-related HCC - Chiao-Ling Li; Chia-Lang Hsu; You-Yu Lin; Ming-Chih Ho; Rey-Heng Hu; Sheng-Tai Tzeng; Ya-Chun Wang; Yasuhito Tanaka; Pei-Jer Chen; Shiou-Hwei Yeh (Journal of Biomedical Science, 2025)
Abstract Background In regions with a high prevalence of chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infections, coinfected patients face a heightened risk of developing hepatocellular carcinoma (HCC), termed HBV/HCV-related HCC (HBCV-HCC). We aimed to investigate the contribution of preexisting chronic hepatitis B (CHB) and subsequent chronic hepatitis C (CHC) to the development of HBCV-HCC. Methods We examined HBV’s involvement in 93 HBCV-HCC cases by analyzing HBV DNA integration as an indicator of HCC originating from HBV-infected hepatocytes, compared with 164 HBV-HCCs and 56 HCV-HCCs as controls. Results Next generation sequencing revealed that 55% of HBCV-HCCs exhibited clonal HBV integration, which falls between the rates observed in HBV-HCCs (88%) and HCV-HCCs (7%), with similar integration patterns to HBV-HCCs. Common HCC somatic mutation analysis indicated HCV superinfection in HBCV-HCCs correlated with increased mutation rates in the telomerase reverse transcriptase (TERT) promoter and beta-catenin genes. Transcriptome analysis showed a prevalence of replicating HCV over HBV in HBCV-HCCs, with preexisting HBV exerting a proliferative role. The comparison of clinical characteristics revealed similarities between HBCV-HCC and HCV-HCC patients, including later onset for HBCV-HCC, possibly due to HCV superinfection slowing carcinogenesis. Notably, HBCV-HCCs with the same driver mutation, HBV integration at the TERT promoter, tended to develop later and showed a better prognosis post-tumor resection than HBV-HCCs. Conclusions Our findings shed light on the interplay between preexisting CHB and subsequent CHC in elevating the risk of HBCV-HCC. These insights are crucial for understanding viral etiology-specific carcinogenesis and guiding surveillance policies for HBCV-HCC post-antiviral therapy.